The personalized telemedical system of Obereg for remote patient's monitoring - A. A. Eremenko; N. V. Rostunova; S. A. Budagyan; A. V. Kurnosov (Вестник анестезиологии и реаниматологии)
The objective: to assess the potential use of the personalized telemedical system (PTS) of Obereg to ensure monitoring and constant medical control over the state of vital systems of the patient's body in the hospital, during transportation, and in out-of-hospital conditions.Subjects and methods. The Obereg system was tested in leading Russian clinics through simultaneous measurement of vital activity parameters with other standard patient monitoring systems. Comparative evaluation criteria were the following: functionality, measurement accuracy in comparison with stationary systems, reliability of operation, the impact on the operation of PTS of other equipment in the intensive care unit and possible interference, user friendliness for personnel and patients, and verification of communication capabilities based on field experiments. Additional parameters of the system were also evaluated. The need for it by medical units of the Ministry of Health of Russia was estimated.Results. The operability of the system has been confirmed in clinical conditions for patients of various profiles, including the most severe cases; it was found that the functionality of the system and accuracy of measurement met relevant requirements. It was estimated that the total demand for such systems in Russia might amount to 4,250,000 units.Conclusion. The device can be used for individual and group monitoring in intensive care units, in in-patient settings after transfer from intensive care, during rehabilitation for remote monitoring at home, and during patients' transportation to monitor their condition in case of emergency.